Fundamental analysis of recombinant human epidermal growth factor in solution with biophysical methods. (February 2015) - Kim, Nam Ah; Lim, Dae Gon; Lim, Jun Yeul; Kim, Ki Hyun; Jeong, Seong Hoon
Abstract Correlation of thermodynamic and secondary structural stability of proteins at various buffer pHs was investigated using differential scanning calorimetry (DSC), dynamic light scattering (DLS) and attenuated total reflection Fourier-transform infrared spectroscopy (ATR FT-IR). Recombinant human epithelial growth factor (rhEGF) was selected as a model protein at various pHs and in different buffers, including phosphate, histidine, citrate, HEPES and Tris. Particle size and zeta potential of rhEGF at each selected pH of buffer were observed by DLS. Four factors were used to characterize the biophysical stability of rhEGF in solution: temperature at maximum heat flux (Tm), intermolecular β-sheet contents, zeta size and zeta potential. It was possible to predict the apparent isoelectric point (pI) of rhEGF as 4.43 by plotting pH against zeta potential. When the pH of the rhEGF solution increased or decreased from pI, the absolute zeta potential increased indicating a reduced possibility of protein aggregation, since Tm increased and β-sheet contents decreased. The contents of induced intermolecular β-sheet in Tris and HEPES buffers were the lowest. Thermodynamic stability of rhEGF markedly increased when pH is higher than 6.2 in histidine buffer where Tm of first transition was all above 70 °C. Moreover, rhEGF in Tris buffer was more thermodynamically stable than in HEPES with higher zeta potential. Tris buffer at pH 7.2 was concluded to be the most favorable.